Constructing “Classical” Philosophy: Cicero and the Epicureanism - Beltrão, Claudia (Revista Archai, 2020)
Cicero’s philosophical works put on the scene intellectual debates among members of the Roman élite, displaying a balanced combination of intellectual skills, moral excellence and political expertise. Greek philosophy emerges as an important ally in Cicero's intellectual project, but not in toto. This paper deals with ways in which Cicero dismisses a multitudo of philosophers who churn out what he considers dangerous and stylistically inferior works. In this way, Cicero contributed to the creation of a “classical” philosophy that still guides modern study of philosophy.